EPICARDIAL ADIPOSE TISSUE THICKNESS - AN ALTERNATIVE TO WAIST CIRCUMFERENCE AS A STAND-ALONE OR SECONDARY MAIN CRITERION IN METABOLIC SYNDROME DIAGNOSTICS? - M. A. Druzhilov; Yu. E. Beteleva; T. Yu. Kuznetsova (Российский кардиологический журнал)
Aim. To assess the potential of echocardiographically assessed epicardial adipose tissue (EAT) thickness as a predictor of high cardiovascular risk (CVR) and subclinical target organ damage (STOD) in patients with abdominal obesity (AO). Material and methods. In 132 normotensive AO patients (mean age 45,0±5,3 years), the following parameters were assessed: lipid and carbohydrate profile, glomerular filtration rate, microalbuminuria, and CVR levels by the SCORE scale. Triplex ultrasound of brachiocephalic arteries, echocardiography, bifunctional 24-hour blood pressure monitoring and arterial stiffness assessment were also performed.Results. Mean levels of EAT thickness were significantly different across age groups (4,2±1,0 mm in those aged 31-45 years vs. 5,1±1,1 mm in those aged 46-55 years; р<0,001). Metabolic syndrome (MS) was diagnosed in 74 (56,1%) patients, based on the presence of AO and 2 additional criteria. In this group, the prevalence of STOD was relatively low. The combination of AO and EAT thickness >75% percentile for each age group (4,8 mm for 31-45-year-olds and 5,8 mm for 46-55-year-olds) was regarded as an alternative predictor of high CVR and STOD, observed in 38 (28,8%) patients. These individuals demonstrated a significantly higher prevalence of STOD (microalbuminuria, carotid atherosclerosis, carotid wall hypertrophy, left ventricular hypertrophy, and increased arterial stiffness). The alternative prognostic model was significantly more effective than the conventional one in terms of the identification of individuals with subclinical carotid atherosclerosis. Conclusion. The alternative model for predicting high CVR and STOD in AO patients, which included the combination of such criteria of visceral obesity as AO and EAT thickness >75% percentile for each age group (4,8 mm for those aged 31-45 years and 5,8 mm for those aged 46-55 years), did not perform any worse than the conventional MS model. Of note, the alternative markers of visceral obesity were significantly more prevalent in patients who had both sets of criteria. AO patients with EAT thickness >75% percentile require further screening for carotid atherosclerosis.